Auxin promotes the transition from chloronema to caulonema in moss protonema by positively regulating PpRSL1and PpRSL2 in Physcomitrella patens - Jang, G; Dolan, L (2011)
• Protonemata are multicellular filamentous networks that develop following the germination of a haploid moss spore and comprise two different cell types - chloronema and caulonema. The ROOT HAIR DEFECTIVE SIX-LIKE1 (PpRSL1) and PpRSL2 basic helix-loop-helix transcription factors and auxin promote the development of caulonema in Physcomitrella patens but the mechanism by which these regulators interact during development is unknown. • We characterized the role of auxin in regulating the function of PpRSL1 and PpRSL2 in the chloronema-to-caulonema transition during protonema development. • Here, we showed that a gradient of cell identity developed along protonemal filaments; cells were chloronemal in proximal regions near the site of spore germination becoming progressively more caulonemal distally as filaments elongated. Auxin controlled this transition by positively regulating the expression of PpRSL1 and PpRSL2 genes. Auxin did not induce caulonemal development in Pprsl1Pprsl2 double mutants that lack PpRSL1 and PpRSL2 gene activity while constitutive co-expression of PpRSL1 and PpRSL2 in the absence of auxin was sufficient to program constitutive caulonema development. • Together, these data indicate that auxin positively regulates PpRSL1 and PpRSL2 whose expression is sufficient to promote caulonema differentiation in moss protonema. © 2011 New Phytologist Trust.